Affiliation history and age similarity predict alliance formation in adult male bottlenose dolphins. (28th November 2019) - Gerber, Livia; Connor, Richard C; King, Stephanie L; Allen, Simon J; Wittwer, Samuel; Bizzozzero, Manuela R; Friedman, Whitney R; Kalberer, Stephanie; Sherwin, William B; Wild, Sonja; Willems, Erik P; Krützen, Michael
Abstract: Male alliances are an intriguing phenomenon in the context of reproduction since, in most taxa, males compete over an indivisible resource, female fertilization. Adult male bottlenose dolphins ( Tursiops aduncus ) in Shark Bay, Western Australia, form long-term, multilevel alliances to sequester estrus females. These alliances are therefore critical to male reproductive success. Yet, the long-term processes leading to the formation of such complex social bonds are still poorly understood. To identify the criteria by which male dolphins form social bonds with other males, we adopted a long-term approach by investigating the ontogeny of alliance formation. We followed the individual careers of 59 males for 14 years while they transitioned from adolescence (8–14 years of age) to adulthood (15–21 years old). Analyzing their genetic relationships and social associations in both age groups, we found that the vast majority of social bonds present in adolescence persisted through time. Male associations in early life predict alliance partners as adults. Kinship patterns explained associations during adolescence but not during adulthood. Instead, adult males associated with males of similar age. Our findings suggest that social bonds among peers, rather than kinship, play a central role in the development of adult male polyadic cooperation in dolphins. Abstract : Multilevel cooperation in adult male bottlenose dolphins is based on friendships that are formed among similarly aged males during their adolescence. Although cooperative behaviors in many animals are found among relatives, this is not the case in dolphins. Our findings reveal the existence of enduring friendships in a complex marine mammal society, similar to those that have been described in many primate species including humans.